Observatorio jurídico para la vigilancia y protección de derechos colectivos. - Mendoza, Pablo R. (2018)
According to the activities planned for the Legal Observatory project of the University of Otavalo, in the month of May of the year 2019, together with the beginning of the semester, developed the training activities with the students assigned to this project; sayings workshops corresponded to the introductory themes on what is the Observatory. its mission, vision, lines of research and methodology; likewise I know gave two workshops related to gender violence by teachers Danny Cifuentes and Pablo Mendoza, for this purpose, students participated. This first activity. (There are the presentations of the four workshops). Already for the month of June with the group of students trained, it was developed and promote a second activity with the National Consejo de Competencias CNC, product of the existing agreement with it. There the Rural Parochial GAD of Imbabura under the joint interaction between CNC officials, teachers from the University of Otavalo and students attached to the observatory, the objective was the application of five formats prepared by the CNC (There are coordination letters and the formats applied). By September, the Observatory participated with its students in various activities in the Seminar on Human Mobility under the direction of the MSC. Andrea Subia and MSc. Javier Pinto. Finally, in November the teachers of the observatory participated in the CIPRI and the IAEN in a panel on Human Mobility. (They include the Certificate of attendance). By 2020, the project will be reformulated as the Legal Observatory for Human Rights Humans of the U.O.